Bidirectional interdomain crosstalk in a Porphyromonas gingivalis chimeric enzyme coordinates catalytic synergy for aromatic amino acid biosynthesis - Yu, Yiyan; An, Jing; Bai, Yu; Xu, Qinghua (Frontiers in Microbiology, 2025)
The shikimate pathway, critical for bacterial aromatic amino acid biosynthesis, represents a prime therapeutic target due to its absence in humans. This study elucidates the structural and functional interplay within the bifunctional enzyme DAH7PS-CM from Porphyromonas gingivalis (PgiDAH7PS-CM), a keystone periodontal pathogen. Integrating AlphaFold3-predicted models with biochemical validation, we identified two interdomain interfaces: a conserved DAH7PS dimerization interface and a polar interaction-driven D-CM interface (e.g., E287/R291). Mutagenesis of these residues and exposure to high Na+ concentrations disrupted enzyme function, confirming polar networks mediate domain crosstalk. The DAH7PS domain’s dimerization relies on conserved interfaces homologous to monofunctional DAH7PS enzymes, while the CM dimer substitutes structural roles through distinct interfacial features. Phylogenetic analysis indicates DAH7PS-CM’s specificity to periodontal pathogens, suggesting adaptive selection for domain fusion to synchronize catalytic steps. Our findings highlight the D-CM interface as a nexus for quaternary stability and allosteric communication, enabling coordinated pathway flux. These insights provide a structural basis for targeting interfacial networks with salt-modulating inhibitors or engineered disruptors, offering novel strategies to impede bacterial virulence and biofilm-associated infections.